2021
DOI: 10.1063/5.0056182
|View full text |Cite
|
Sign up to set email alerts
|

Internal conversion of singlet and triplet states employing numerical DFT/MRCI derivative couplings: Implementation, tests, and application to xanthone

Abstract: We present an efficient implementation of nonadiabatic coupling matrix elements (NACMEs) for density functional theory/multireference configuration interaction (DFT/MRCI) wave functions of singlet and triplet multiplicity and an extension of the Vibes program that allows us to determine rate constants for internal conversion (IC) in addition to intersystem crossing (ISC) nonradiative transitions. Following the suggestion of Plasser et al. [J. Chem. Theory Comput. 12, 1207 (2016)], the derivative couplings are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 77 publications
0
24
0
Order By: Relevance
“…330 ps. Recently, Bracker et al extended the use of Fermi’s golden rule for both the internal conversion and the ISC . Their results suggested that 1 ππ*– 3 ππ* ISC and 1 ππ*– 1 nπ* IC are competitive processes from which a branched mechanism was inferred.…”
mentioning
confidence: 99%
“…330 ps. Recently, Bracker et al extended the use of Fermi’s golden rule for both the internal conversion and the ISC . Their results suggested that 1 ππ*– 3 ππ* ISC and 1 ππ*– 1 nπ* IC are competitive processes from which a branched mechanism was inferred.…”
mentioning
confidence: 99%
“…A further advantage of the Fourier transform approach is that it is easily extended to include temperature effects by assuming a Boltzmann population of the vibrational levels in the initial electronic state. 35,41,42 To speed up the numerical integration, a Gaussian damping function is introduced. The width of the damping function, the integration interval, and the number of grid points are technical parameters that have to be chosen with great care.…”
Section: ■ Computational Methodsmentioning
confidence: 99%
“…For IC, only the linear coupling terms of the nonadiabatic corrections were taken into account. The gradients of the matrix elements and the derivative couplings were obtained by distorting the nuclear framework along dimensionless normal modes using a step size of 0.5 units, utilizing averaged two-point finite difference techniques. , The phases of these gradients are arbitrary and need to be aligned properly by relating the phases of the molecular orbitals and of the DFT/MRCI wavefunctions to a reference calculation as performed in earlier work . Evaluation of nonradiative rate constants in the energy domain according to is not practicable for molecules as large as those investigated here because the density of vibrational states is too high.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method was originally conceived as a means to calculate singlet and triplet valence excited states of organic molecules. However, the scope of the method has recently been significantly widened to include multiplicity-independent formulations, , a parameterization tuned to the description of transition-metal complexes, the treatment of core-excited states, and the calculation of spin–orbit and nonadiabatic couplings ,, and diabatic potentials …”
Section: Introductionmentioning
confidence: 99%